2020
DOI: 10.3390/molecules25245923
|View full text |Cite
|
Sign up to set email alerts
|

7-Isopentenyloxycoumarin: What Is New across the Last Decade

Abstract: 7-Isopentenyloxycoumarin is among the most widespread naturally occurring prenyloxy umbelliferone derivatives. This secondary metabolite of mixed biosynthetic origin has been typically isolated from plants belonging to several genera of the Rutaceae and Apiaceae families, comprising widely used medicinal plants and in general plants with beneficial effects on human welfare, as well as edible fruits and vegetables. Although known for quite a long time (more than 50 years), only in the last two decades has this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As reported in Figure 1 , employing a 2D culture system, hOBs isolated from osteoporotic patients ( n = 10, median age 80.3 ± 11.9) were used to test the effects of the four different coumarin derivatives umbelliferon (UF), aurapten (AU), 7-isopentenyloxycoumarin (7-ISO) and umbelliprenin (UP) ( Supplementary Figure S1 ), whose natural sources and chemical synthetic methods have been recently reviewed. In detail, UF was purchased commercially (Sigma-Aldrich, St. Louis, MO, USA), while 7-ISO, AU, and UP were obtained via chemical synthesis following the route reported in [ 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…As reported in Figure 1 , employing a 2D culture system, hOBs isolated from osteoporotic patients ( n = 10, median age 80.3 ± 11.9) were used to test the effects of the four different coumarin derivatives umbelliferon (UF), aurapten (AU), 7-isopentenyloxycoumarin (7-ISO) and umbelliprenin (UP) ( Supplementary Figure S1 ), whose natural sources and chemical synthetic methods have been recently reviewed. In detail, UF was purchased commercially (Sigma-Aldrich, St. Louis, MO, USA), while 7-ISO, AU, and UP were obtained via chemical synthesis following the route reported in [ 28 , 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…7-isopentenoxycoumarin ( Figure 6D ), a natural pentenoxyumbelliferone derivative widely found in Rutaceae and umbelliferaceae, is a floral extract of Amaranthus retroflexus L., which is used as a food product in southern and central Italy ( Fiorito et al, 2017 ). Studies have shown that 7-isopentenyloxycoumarins have antifungal, antioxidant, anticancer, neuroprotective, and anti-inflammatory properties ( Preziuso et al, 2020 ). Fiorito et al found that 7-isopentenoxycoumarin significantly induced melanogenesis at a dose of 40 μm, with the highest induction of melanin at 72 h, and excitingly the induction was 6-fold greater than that of the control group, and the mechanism of action was to increase melanogenesis by elevating MITF and its downstream genes tyrosinases, TRP-1 and Trp-2.…”
Section: Glycosidesmentioning
confidence: 99%
“…Both compounds 1 and 4 are thought to be precursors of known biologically active O-prenyl cinnamic acids, like boropinic acid 2, 4′-geranyloxyferulic acid 3, and coumarins like 7-isopentenyloxycoumarin 5, auraptene 6, and umbelliprenin 7. The importance and great potential of all these five oxyprenylated secondary metabolites have been recently exhaustively reviewed [13][14][15][16]. Furthermore, studies like the one described herein and the few ones published in the last 5 years are of great importance to explore the possibility and to claim biomasses from cultured calli as a more convenient, easier to handle, and alternative route to obtain higher quantities of oxyprenylated secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%